Commonwealth Secretariat programmes of assistance : practice and procedures : a manual for points of contact and others in Commonwealth governments (The Secretariat LondonGB, 1999)
Provides a brief background of the Secretariat's programmes of work, its structure and the funds that support its work. Supplies practical information on the work of each division of the Secretariat, with focus on technical and other assistance managed and executed by them for the benefit of member governments, and on ways of accessing it.
DC